Farmer Field Days Report in Makueni and Kitui Counties - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Farmer field days were held in Makueni and Kitui Counties to showcase performance of improved drought-tolerant crop varieties - pearl millet, sorghum, pigeon pea and beans - under conventional and conservation tillage systems. The events drew diverse stakeholders including government officials, agro-dealers, seed merchants, farmers' organizations and financial institutions. Through farm walks and interactive sessions, farmers gained firsthand insights into the comparative performance of crops under the two tillage systems gaining insights on crop management for improved yields. The convergence of various stakeholders provided farmers with an invaluable platform for acquiring extensive knowledge from actors across the agricultural value chain, emphasizing the importance of collaborative efforts in promoting sustainable agricultural practices and fostering growth within the sector.